A study of heat and mass transfer micropolar fluid flow near the stagnation regions of an object. (August 2021) - Salahuddin, T.; Khan, Mair; Al-Mubaddel, Fahad S.; Alam, Mohammad Mahtab; Ahmad, Irfan
Abstract: The main objective of this analysis is to present an unsteady magneto-micropolar fluid throw towards a circular object. An impulsive flow is assumed at a very large distance from object which is known as free stream region. The free stream region is perpendicular to the object in upward direction. Due to this phenomena, body forces are taken in the form of convection. In this problem, the object is assumed to be extremely heated which take us towards two main assumptions: i) assisting flow is taken and opposing flow is neglected and ii) radiation factor appears. The free stream flow is so dominant that it touches all external sides of the object which gives a good mathematical study of the stagnation regions (forward and rare) and the remaining points in which fluid particles touch the object. The different situations are assumed at different angles to analyze the flow, temperature, microrotation and concentration distributions. But our main focus will be rare and forward stagnation points. Heat generation and chemical reaction influence are also studied for such complex formulation. A magnetic field is applied to align these fluid particles motion. The so-called non-similar transformations and boundary layer approximation are used to obtain the very complex highly non-linear partial differential system depending on three independent variables. A second order convergent scheme known as Keller box is implemented to calculate the solution of the system. The results for separation time around the cylinder are calculated in tabular form. Moreover, graphical behavior is examined for forward and rare stagnation points for concentration, microrotation, velocity and temperature distributions. A comparative analysis is executed from previous data for different values of separation time.